The growth of US top income inequality: A hierarchical redistribution hypothesis - Blair Fix (Forum on Capital As Power - Toward a New Cosmology of Capitalism, 2018)
What accounts for the growth of US top income inequality? This paper proposes a hierarchical redistribution hypothesis. The idea is that US firms have systematically redistributed income to the top of the corporate hierarchy. I test this hypothesis using a large scale hierarchy model of the US private sector. My method is to vary the rate that income scales with hierarchical rank within modeled firms. I find that this model is able to reproduce four intercorrelated US trends: (1) the growth of the top 1% income share; (2) the growth of the CEO pay ratio; (3) the growth of the dividends share of national income; and (4) the "fattening" of the entire income distribution tail. This result supports the hierarchical redistribution hypothesis. It is also consistent with the available empirical evidence on within-firm income redistribution.
Keywords: B5; C5; D31; D33; 330; top income share; inequality; hierarchy; power; functional income distribution; personal income distribution